Lo Batèu de pèira, ou la recherche des signes - Marie-Jeanne Verny (Revue des Langues Romanes)
Lo Batèu de pèira: two main places, Nîmes and Africa; several main periods of the 20th century. Space and time are intertwined throughout the story. This article attempts to decipher, through an apparent narrative complexity, the signs scattered by the author, between masks and unveiling, which reconstitute, in bits and pieces, a long-concealed reality.